Transformative and cognitive approaches to information retrieval and security procedures. (9th June 2020) - Ogiela, Urszula
Summary: Transformative computing is a new area of computer technologies. It is also a new paradigm, which allows to join wireless communication with sensor networks and artificial intelligence technologies. It considerably enhances computing possibilities, increases efficiency of data exploration and analysis, as well as information retrieval using sensors or augmented cognition. In this article, we describe possible applications of cognitive security protocols for such computing application, especially focused on security, and data exploration in distributed systems. Also will be presented the impact of cognitive protocols for securing wireless systems and sensors infrastructures.